2022
DOI: 10.1097/md.0000000000032355
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of acupunture treatment on autonomic nerve dysfunction in convalescent period of stroke based on heart rate variability assessment technique

Abstract: Stroke patients with autonomic dysfunction are more likely to develop cardiac problems, which have been linked to lower functional outcomes and increased mortality. In this study, heart rate variability (HRV) detection paired with the Clinical Feature Scale will be utilized to elucidate the immediate impact of manual acupuncture on autonomic dysfunction of varying severity in the convalescence stroke phase. This is a randomized, single-blind, controlled clinical trial approach. At a ratio of 1:1, 60 appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Several randomized controlled trials (RCTs) have been conducted on electroacupuncture (EA) and manual acupuncture stimulation. Although the duration and frequency of interventions vary, these results support the clinical efficacy of acupuncture in improving motor dysfunction after IS [22,39–41,44–48] . In particular, acupuncture may improve patients’ National Institute of Health stroke scale (NIHSS) scores and the ability to perform activities of daily living.…”
Section: Evidence From Clinical Studiesmentioning
confidence: 73%
“…Several randomized controlled trials (RCTs) have been conducted on electroacupuncture (EA) and manual acupuncture stimulation. Although the duration and frequency of interventions vary, these results support the clinical efficacy of acupuncture in improving motor dysfunction after IS [22,39–41,44–48] . In particular, acupuncture may improve patients’ National Institute of Health stroke scale (NIHSS) scores and the ability to perform activities of daily living.…”
Section: Evidence From Clinical Studiesmentioning
confidence: 73%
“…Characteristics of the included ongoing studies [ 43 , 44 , 45 , 46 , 47 , 48 , 49 ] and the studies without accessible/published results [ 50 , 51 , 52 , 53 , 54 ] are shown in Tables S2 and S3 of the Supplementary Materials .…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies with published results are presented in Table 1. Characteristics of the included ongoing studies [43][44][45][46][47][48][49] and the studies without accessible/published results [50][51][52][53][54] are shown in Tables S2 and S3 of the Supplementary Materials.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%